Rural and Urban/Suburban Victim Professionals’ Perceptions of Gender-Based Violence, Victim Challenges, and Safety Advice During the COVID-19 Pandemic - Lynch, Kellie R. (Violence against women, 2023)
This study surveyed a national sample of victim service professionals (N = 222) and compared rural versus urban/suburban participants’ perceptions of a variety of issues, such as the impact of the pandemic on gender-based violence victimization and safety advice for isolated victims. Increased interference with victim employment and the abuser monitoring of online activities were reported by participants across all communities. However, urban/suburban participants rated the magnitude of all victim challenges as greater, while more rural participants noted child abuse as a particular problem in their communities. The results highlight the importance of community context for improving coordinated responses to gender-based violence (n = 101).